Decision Support System for Natural Rubber Supply Chain Management Performance Measurement: A Sustainable Balanced Scorecard Approach - Marimin Marimin; Adhi Wibisono; M Arif Darmawan (International Journal of Supply Chain Management, 2017)
Abstract Performance evaluation and decision making application on natural rubber agro industry productivity improvement along its supply chain is a complex and uncertain processes which needs decision support system (DSS). The research objectives were threefold in nature, i.e. (1) analyze natural rubber supply chain decision-making models, (2) formulate performance measurement model by using sustainable balanced scorecard approach and (3) develop decision support system prototype using systems approach. The DSS model consisted of four sub-models, i.e. supply chain performance measurement using sustainable balanced scorecard approach and Fuzzy Analytical Hierarchy Process (F-AHP); latex quality improvement strategy selection using F-AHP; prospective product selection using Exponential Comparison Technique; and supply chain performance improvement strategy selection using Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis. The developed DSS was implemented and tested by using real cases at Indonesia natural rubber industries. This research gave promising result in improving the natural rubber industry supply chain management performance. Keywords: DSS, Supply Chain, Natural Rubber, Sustainable Balanced Scorecard, Fuzzy AHP